Efficacy of multimodal rehabilitation strategies on gastrointestinal function recovery in postoperative aortic dissection patients: a narrative review - Xiao, Jing-Hua; Wei, Jing-Xue; Bi, Zi-Ting; Huang, Lang; Dai, Yuan-Hong; Zhang, Yun-Shan (Frontiers in Physiology, 2025)
Aortic dissection is associated with significant postoperative gastrointestinal dysfunction, a common complication that adversely affects patient prognosis. Recent advancements in multimodal rehabilitation strategies have shown promise in enhancing postoperative gastrointestinal recovery, but their impact on gastrointestinal function recovery in patients after aortic dissection surgery remains unclear. The narrative review evaluates the efficacy of multimodal rehabilitation strategies on gastrointestinal function recovery in postoperative aortic dissection patients. It provides an overview of the associated pathological mechanisms and fundamental elements of multimodal rehabilitation strategies, assesses the existing clinical evidence, investigates tailored applications for specific populations, and identifies barriers and solutions to implementation. Current evidence indicates that multimodal rehabilitation strategies positively influence the recovery of gastrointestinal function in patients following aortic dissection surgery. Current evidence remains constrained by a scarcity of high-quality, large-sample randomized controlled trials specific to this population, and mechanistic understanding continues to rely heavily on extrapolation from non-cardiac surgery studies. Future efforts should integrate biomarkers, precision medicine, intelligent monitoring systems, and standardized protocols to enable large-scale multicenter randomized controlled trials and advance foundational research.